Trends in Maternal Mortality Ratio in a Tertiary Referral Hospital and the Effects of Various Maternity Schemes on It. - Harpreet Kaur; Sharanjit Kaur; Sukhwinderjit Singh (Tehran University of Medical Sciences, 2015)
Objective:To analyze the trend in maternal mortality ratio in a tertiary care centre and the effect of various maternity schemes on it. Materials and methods: Retrospective analysis of all maternal deaths occurring in the Guru Gobind Singh Medical College & Hospital, Faridkot, Punjab, India was done from Jan 2010 to Dec 2012. Every maternal death was scrutinized from various aspects like direct cause of death, age, locality, antenatal care and gestational age. Results:The total number of deliveries has risen from 957 in 2010 to 1063 in 2012 at the same time the maternal mortality ratio has increased from 835.94 in 2010 to 2054.55 per one live birth in 2012. Haemorrhage (24.12%) and sepsis (18.9%) were the most common causes of death followed closely by pregnancy induced hypertension including eclampsia (15.5%). Anemia (12.06%) contributed to the most common indirect cause of death. Conclusion:Implementation of the various maternity schemes has had no significant impact on the profile of dying mothers. There is a need to stress the importance of good antenatal care in reducing Maternal Mortality Ratio.